PEDAGOGICAL TACTICS: SPECIFICITY OF SPEECH ACTIVITY OF THE PEDAGOGICAL EDUCATOR (ON THE EXAMPLE OF PRESCHOOL EDUCATIONAL THEORIES) - Abdurashidov Adxam Abduxamidovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
in this article, the specificity of the speech activity of the pedagogical educator in preschool education and the acquisition of exemplary speech for the educator is an indicator that determines his readiness for his profession. This article discusses the specificity of the speech activity of the pedagogical educator in preschool educational organizations.